Estimating the Impact of Exchange Rate Volatility on Exports: A Comparative Study of Sri Lanka and Bangladesh - Thuvaraka, T.; Karunaanithy, K. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
This study investigates the impact of exchange rate volatility on exports in Sri Lanka and Bangladesh using quarterly data from the first quarter of 2000 to the fourth quarter of 2023. The Autoregressive distributed lag (ARDL) bounds testing approach is applied to examine both long-run and short-run relationships between exchange rate volatility and exports. The moving average standard deviation method is employed to calculate exchange rate volatility. Data for this study were sourced from CBSL, Bangladesh Bank and the IMF. The analysis confirms that in the long-run, exchange rate volatility significantly reduces exports in Sri Lanka, while in Bangladesh the effect is negative but statistically insignificant. Conversely, Real foreign income positively influences exports in both countries, highlighting its role in driving exports. In Sri Lanka, the real effective exchange rate significantly lowers exports, while relative prices also have a positive but insignificant. In the case of Bangladesh, relative prices also have a positive but insignificant. In the short run, exchange rate volatility significantly reduces exports in Bangladesh, while real foreign income continues to positively affect exports in both countries. Moreover, the relative price positively and significantly impacts exports in Sri Lanka, while for Bangladesh has negative impact. Further, in Bangladesh, the real effective exchange rate significantly and positively affects on exports, suggest exchange rate depreciation negatively impacts exports in the short-run. The results indicate that the models used are robust, reliable and stable over the study period. These findings suggest some policy implications for effectively managing the exchange rate system and sustainably promoting exports of both Sri Lanka and Bangladesh.
Keywords: ARDL bounds testing; Exchange rate; Export; Volatility